The specific responses to mechanical wound in leaves and roots of Catharanthus roseus seedlings by metabolomics. Issue 1 (1st January 2018) - Chen, Qi; Lu, Xueyan; Guo, Xiaorui; Liu, Jia; Liu, Yang; Guo, Qingxi; Tang, Zhonghua
ABSTRACT: The mechanical wound is one of the unavoidable threats to survival of plants. More researchers focus on the effect of mechanical wound to the over-ground tissues. And the effects of wound to roots were frequently ignored, although it is an important organ for plant growth. In our studies, the metabolomics study was performed to reveal the mechanical wound effects in Catharanthus roseus on roots and leaves by combining gas chromatography-mass spectrometer (GC-MS), liquid chromatograph-mass spectrometer (LC-MS) and statistical analyses. The metabolic response of TIAs and PCs in plants to wound was most active at 0.5 h after treatment via Q value analysis. At this time point, then significantly responsive primary metabolites and specific secondary compounds (TIAs and PCs) were screened by PLS-DA score plot. In this case, the treatments of CK, LT (wound to leaves) and RT (wound to roots) were clearly distinguished. The targeted compounds include 8 sugars, 4 TIAs and 12 PCs and they displayed specific responses to CK, LT and RT treatments. Under RT group, plants invest more resources on the local responses using TIAs and the color reactions to regulate wound close using PCs. Whereas, LT group might lay emphasis on systemic responses via TIAs induced by SA (salicylic acid) and gallic acid. Our studies provide some basic data for further investigations of the defensive mechanism on roots treated by mechanical wound.